2014
DOI: 10.1097/jto.0000000000000094
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Reveals a Novel NSCLC ALK F1174V Mutation and Confirms ALK G1202R Mutation Confers High-Level Resistance to Alectinib (CH5424802/RO5424802) in ALK-Rearranged NSCLC Patients Who Progressed on Crizotinib

Abstract: Acquired secondary mutations in the anaplastic lymphoma kinase (ALK) gene have been identified in ALK-rearranged (ALK+) non-small-cell lung cancer (NSCLC) patients who developed disease progression while on crizotinib treatment. Here, we identified a novel secondary acquired NSCLC ALK F1174V mutation by comprehensive next-generation sequencing in one ALK+ NSCLC patient who progressed on crizotinib after a prolonged partial response to crizotinib. In a second case, we identified a secondary acquired ALK G1202R,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 15 publications
3
117
0
Order By: Relevance
“…Many other resistance mutations have been described [Sasaki et al 2011;Katayama et al 2012;Doebele et al 2012;Ignatius Ou et al 2014]. Moreover, copy number gains of the ALK fusion gene [Katayama et al 2011] and bypass track activation involving NSCLC drivers such as EGFR, c-KIT and KRAS [Sasaki et al 2011;Doebele et al 2012;Katayama et al 2012] have been reported.…”
Section: Secondary or Acquired Resistancementioning
confidence: 99%
“…Many other resistance mutations have been described [Sasaki et al 2011;Katayama et al 2012;Doebele et al 2012;Ignatius Ou et al 2014]. Moreover, copy number gains of the ALK fusion gene [Katayama et al 2011] and bypass track activation involving NSCLC drivers such as EGFR, c-KIT and KRAS [Sasaki et al 2011;Doebele et al 2012;Katayama et al 2012] have been reported.…”
Section: Secondary or Acquired Resistancementioning
confidence: 99%
“…However, ceritinib inhibits I1171T [136]. G1202R is an acquired mutation that drives crizotinib resistance but has also been demonstrated to confer high-level in vitro and in vivo resistance to alectinib and ceritinib [137]. A case of MET amplification has been reported in an alectinib-resistant tumor.…”
Section: Cns Penetrationmentioning
confidence: 99%
“…Other acquired ALK kinase mutations that confer resistance to crizotinib include C1156Y, L1152R, I1171T, S1206Y, F1174L and G1269A [131,[133][134][135][136]. The G1202R crizotinib-resistance mutation also confers resistance to second generation ALK TKIs [137]. Increase in ALK copy number has also been demonstrated in patients who develop crizotinib resistance [132].…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…This variant may be linked to the ALK inhibitors resistance since the contact maintained by methionine residue M-1199 is most important for the effective binding and stability of the ALK-crizotinib complex [19]. The neighbouring region includes also the sites of secondary acquired ALK alterations L1996M and L1998P in EML4-ALK fusion positive lung cancers which confer resistance to crizotinib, and G1202R, which confers resistance to a second-generation ALK inhibitor alectinib and other ALK inhibitors [4,7,14,15]. Therefore, a precise character of the detected variant is critical for further therapeutic considerations.…”
Section: B Amentioning
confidence: 99%